"Hot spots" growth on single nanowire controlled by electric charge. Issue 23 (31st May 2016) - Xi, Shaobo; Liu, Xuehua; He, Ting; Tian, Lei; Wang, Wenhui; Sun, Rui; He, Weina; Zhang, Xuetong; Zhang, Jinping; Ni, Weihai; Zhou, Xiaochun
Abstract : We studied the "hot spots" on single Ag nanowires in galvanic replacement reaction by dark-field microscopy. We found that electric charge controls the formation, composition and distribution of "hot spots" in charge coupled reaction. Abstract : "Hot spots" – a kind of highly active site, which are usually composed of some unique units, such as defects, interfaces, catalyst particles or special structures – can determine the performance of nanomaterials. In this paper, we study a model system, i.e. "hot spots" on a single Ag nanowire in the galvanic replacement reaction (GRR), by dark-field microscopy. The research reveals that electric charge can be released by the formation reaction of AgCl, and consequently the electrochemical potential on Ag nanowire drops. The electric charge could induce the reduction of Ag + to form the "hot spots" on the nanowire during the GRR. The appearance probability of "hot spots" is almost even along the Ag nanowire, while it is slightly lower near the two ends. The spatial distance between adjacent "hot spots" is also controlled by the charge, and obeys a model based on Boltzmann distribution. In addition, the distance distribution here has an advantage in electron transfer and energy saving. Therefore, it's necessary to consider the functions of electric charge during the synthesis or application of nanomaterials.